Player-Character Relationship and Game Satisfaction in Narrative Game: Focus on Player Experience of Character Switch in The Last of Us Part II - Erb, Valérie; Lee, Seyeon; Doh, Young Yim (Frontiers in Psychology, 2021)
While player characters (PCs) are the key element in engaging players in narrative games, the player’s experience and relationship with the PC have received scarce attention from the perspective of the subjective player experience. The diversity of players and the importance of the PC in the game suggests meaningful connections between how players relate to their PC and the resulting satisfaction with the game. We therefore investigated in this study how the player-character relationship influences the player’s satisfaction with the game. We performed semi-structured in-depth interviews with 12 players of The Last of Us Part II, a game which has elicited highly polarized reactions in relation to how players responded to a switch of the game’s PC. Through thematic analysis three themes were found, illustrating the connection between aspects of the player-character relationship and the overall game satisfaction. The themes are 'Tolerance of forced character switch’, ‘Malleability of character image’ and ‘Flexibility of character attachment’. We discuss how those findings should be taken into consideration when designing diverse and meaningful gaming experiences.